Factors determining the level of non-financial disclosure - an analytical study of companies registered in the financial markets of the Kingdom of Saudi Arabia - benhalima, fethi; boukredid, abdelkadir (Journal of Research in Finance and Accounting, 2023)
This study aims to identify the factors determining the level of disclosure of non-financial information through an analytical study of the annual financial reports of companies registered in the financial markets of the Kingdom of Saudi Arabia.The study concluded a set of results, most notably the absence of a statistically significant effect of the level of training and the size of the privileges granted at the general level, the disclosure of non-financial information, unlike the rest of the characteristics.